PENGARUH OTHER COMPREHENSIVE INCOME, KARAKTERISTIK KOMITE AUDIT DAN KUALITAS AUDIT TERHADAP REAL EARNING MANAGEMENT DENGAN LEVERAGE SEBAGAI VARIABEL MODERASI - Dimas Rahmat Hidayat; Deden Afriyanto Perdana; Sekar Mayangsari; Lin Oktris (Jurnal Magister Akuntansi Trisakti, 2021)
This study aims to analyze the effect of Other Comprehensive Income, Audit Committee Characteristics and Audit Quality on Real Earning Management with Leverage as Moderating Variable. The data used are secondary data obtained from the financial statements of manufacturing companies listed on the Indonesia Stock Exchange. This research is a research conducted by testing the hypothesis. A total of 216 samples from 57 companies with an observation period of 4 years, 2016-2019 were selected using the Data Cross Sections method. The analytical method used to test the hypothesis in this study is multiple linear regression analysis. The results of this study indicate that Other Comprehensive Income Variables, audit committee financial expertise, audit committee tenure, number of audit committee meetings and audit quality do not have a negative effect on real earning management while financial leverage variable has a positive effect on real earnings. management, and the financial leverage variable was not able to weaken the negative influence of the Other Comprehensive Income variable, the variable financial expertise/ financial expertise of the audit committee, the tenure of the audit committee, the number of audit committee meetings and audit quality on real earnings management.